PERIAPICAL CYST: CUNICAL CASE REPORT - Silva Infantes, Manuel (2004)
This article shows clínical, radiographic, and therapeutics fea tu res of Periapical Cyst. It is presented a case report, that Izas a large extension and involve seven teeth, from left mandibular canine ( 3,3) fo right mandibular first bicuspid (4,4). They were previously given root canal treatment.